Estudo de problemas elastodinâmicos bidimensionais no domínio do tempo com elementos de contorno - Julio Cesar Torres Rodriguez (2002)
This work presents a computational tool based on the Boundary Element Method (BEM) with time dependent fundamental solution, for analysis and two-dimensional simulation of elastodynamic problems. This tool called ANELC (Elastodynamics Analysis with Boundary Elements) study the behaviour of the wave propagation in infinite and semi- infinite domains.The implemented algorithm uses isoparametric linear elements facilitating the problem geometry modeling. The boundary integral equations are solved using a time stepping technique, where constant and linear temporal variations are assumed for tractions anddisplacements respectively. The ANELC is an interactive program in all the stages of the analysis.ANELC is a generic tool to treat problems with different geometry contours (twodimensional models) and loadings. The program has an interface of such form friendly and intuitive that becomes the learning more easy. It is practical because is controlled by the user along a sufficiently flexible interactive graphic interface, allowing in all theinstants the visualization of the model and the results, decreasing the errors in the data entry (pre-processing) and improving the visualization of the numerical and graphic information of the results (post-processing).